Strategies for Improving Occupational Safety in the ATBM Weaving Industry - Rahmawati, Nurmalinda; Heikal, Jerry (Universitas Insan Cendekia Mandiri, 2024)
Occupational safety is a crucial aspect of the manufacturing industry, especially in the weaving industry that uses shuttle machines. This study aims to identify risks and develop strategies to prevent occupational accidents in the shuttle weaving industry. The methods used include job safety analysis (JSA) and strategy formation using the IFAS and EFAS matrix to formulate the necessary solutions. The results revealed that seven types of jobs were identified as having 23 potential risks of occupational accidents. The highest risk was found in the shuttle weaving process, where the activities involved have the potential to cause physical injuries such as permanent disability due to being targeted by the weft binoculars during production. The proposed strategies include improving weaknesses by capitalising on existing strengths, implementing new technologies and safety policies to address threats, and improving compliance and incident response to reduce risks. This research is expected to contribute as a reference for the weaving industry with shuttle machines in conducting risk analysis and implementing occupational accident prevention measures.